Spectroscopical study of natural nanostructured carbonaceous material shungite - Konchits, A.A.; Shanina, B.D.; Valakh, M.Ya.; Yanchuk, I.B.; Yukhymchuk, V.O.; Yefanov, A.V.; Krasnovyd, S.V.; Skoryk, M.A. (Functional Materials, 2014)
The correlation between morphology, local structure and magnetic properties of the different origin shungite material with nanocarbon content 25-40 wt. % was studied by SEM, EPR, and Raman scattering methods. It was established that structure of the shungite samples is formed by micron size agglomerations of carbon and silicon dioxide clusters with impregnations of pyrite (FeS₂), iron oxide and aluminium oxide particles. It was found from the Raman data that nanocarbon fraction is formed from sp²-hybridized well ordered carbon clusters, size of which increases from 9 nm up to 12 nm after annealing of the samples. It was found for the first time that origin of L3 and L4 EPR lines is due to oxy-deficiency centers in the silicon dioxide clusters.